Facilitating Healthy Eating in Latin American Restaurants: Examining Acceptability and Barriers Among Restaurant Owners and Staff. (7th June 2021) - Fuster, Melissa; Abreu-Runkel, Rosa; Huang, Terry T-K; Rodriguez, Michelle; Harrison, Elise; Elbel, Brian; Ray, Krishnendu; Handley, Margaret
Abstract: Objectives: Examine the acceptability and potential barriers for the implementation of healthy eating promoting (HEP) strategies in independently-owned Latin American restaurants (LAR), including the influence of the COVID-19 pandemic. Methods: LAR owners and staff were recruited via social media and community networks across the US. Potential participants completed an online survey ( n  = 20) on demographic and restaurant characteristics and current HEP strategies. Subsequently, we conducted semi-structured, online interviews with LAR owners and staff ( n  = 13) to examine attitudes of and barriers to the implementation of HEP strategies. Each verbatim transcript was analyzed by two coders using Dedoose, following an iterative process. Excerpts were rated according to how open respondents were to implement potential strategies (1 = opposed, 2 = neutral, 3 = open). Results: The survey revealed that the most common HEP strategies already in place were offering vegetarian options (80%) and seafood (75%). The interviews asked about additional, potential HEP strategies, showing that the highest rated was the provision of nutrition information, with all excerpts rated as "open" (rate = 3). This was followed by increasing healthy options, notably vegetarian dishes (Mean excerpt rate = 2.9 ± 0.3); menu highlights (2.6 ± 0.9); and promotion of healthier options (2.5 ± 0.7). Portion size changes were rated the lowest (1.1 ± 0.3). The results included barriers identified for each strategy, the influence of COVID-19, and alternative strategies identified. Conclusions: Latin communities present higher dietary risk factors for chronic disease, compared to non-Hispanic Whites. LARs are a significant source of dietary intake and have the potential to positively influence eating behaviors but are seldom engaged by public health. This research aimed to bridge this gap, finding common grounds for potential collaborations benefiting both community health and the wellbeing of these important community institutions. Funding Sources: National Institutes of Health/NHLBI and the Centers for Disease Control and Prevention.